Audiovisual spoken word training can promote or impede auditory-only perceptual learning: prelingually deafened adults with late-acquired cochlear implants versus normal hearing adults - Bernstein, Lynne E.; Eberhardt, Silvio P.; Auer, Edward T. (Frontiers in Psychology, 2014)
Training with audiovisual (AV) speech has been shown to promote auditory perceptual learning of vocoded acoustic speech by adults with normal hearing. In Experiment 1, we investigated whether AV speech promotes auditory-only (AO) perceptual learning in prelingually deafened adults with late-acquired cochlear implants. Participants were assigned to learn associations between spoken disyllabic C(=consonant)V(=vowel)CVC non-sense words and non-sense pictures (fribbles), under AV and then AO (AV-AO; or counter-balanced AO then AV, AO-AV, during Periods 1 then 2) training conditions. After training on each list of paired-associates (PA), testing was carried out AO. Across all training, AO PA test scores improved (7.2 percentage points) as did identification of consonants in new untrained CVCVC stimuli (3.5 percentage points). However, there was evidence that AV training impeded immediate AO perceptual learning: During Period-1, training scores across AV and AO conditions were not different, but AO test scores were dramatically lower in the AV-trained participants. During Period-2 AO training, the AV-AO participants obtained significantly higher AO test scores, demonstrating their ability to learn the auditory speech. Across both orders of training, whenever training was AV, AO test scores were significantly lower than training scores. Experiment 2 repeated the procedures with vocoded speech and 43 normal-hearing adults. Following AV training, their AO test scores were as high as or higher than following AO training. Also, their CVCVC identification scores patterned differently than those of the cochlear implant users. In Experiment 1, initial consonants were most accurate, and in Experiment 2, medial consonants were most accurate. We suggest that our results are consistent with a multisensory reverse hierarchy theory, which predicts that, whenever possible, perceivers carry out perceptual tasks immediately based on the experience and biases they bring to the task. We point out that while AV training could be an impediment to immediate unisensory perceptual learning in cochlear implant patients, it was also associated with higher scores during training.